An Efficient Process for The Synthesis of Anti-Obesity Drug Rimonabant - Seetharama Sarma, P.; Surayanarayana, M.V.; Nageswar Rao, Ch.; Pratap Reddy, Padi; Khalilulah, M.; Praveen, Cherukupally; Kalyan Chakravarthy, Akula (Asian Journal of Chemistry, 2010)
A convenient and cost effective synthetic process has been developed for the synthesis of an anti-obesity drug rimonabant (1). The process involves the condensation of 4-chloro propiophenone with diethyl oxalate to get the diketo ester (3), which upon reaction with N-amino piperidine followed by acid catalyzed cyclization with 2,4-dichloro phenyl hydrazine hydrochloride afforded rimonabant (1) in good overall yield.